The Passion Projects : Modernist Women, Intimate Archives, Unfinished Lives - Micir, Melanie (Book collections on Project MUSE., 2019)
This book examines biographical projects that modernist women writers undertook to resist the exclusion of their friends, colleagues, lovers, and companions from literary history.